2021
DOI: 10.17977/jptpp.v6i12.15179
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Trainer Kits in Project-Based Learning to Improve Critical Thinking, Motivation, and Competency of Electrical Engineering Students

Abstract: <p class="Abstrak"><strong>Abstract:</strong> Innovation of Project-based learning (PjBL) in the 21st century continues to be developed to improve learning outcomes. The use of Trainer kits presents several challenges in achieving learning objectives, both in terms of design, planning, and implementation. The purpose of this study is to implement the Automation of Electrical Installation trainer kit in project-based learning to increase student motivation, critical thinking, and competence. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…This design allowed the students to explore the given biotechnology topics better so that they independently perceived the knowledge that the facilitator had corrected, if necessary. Similar to the present study's finding, Haryudo et al (2021) also conducted project-based learning to increase students' scientific thinking in three learning phases. Students were exposed to trainer kits in their study, so they directly experienced how to utilize such tools.…”
Section: Discussionsupporting
confidence: 71%
“…This design allowed the students to explore the given biotechnology topics better so that they independently perceived the knowledge that the facilitator had corrected, if necessary. Similar to the present study's finding, Haryudo et al (2021) also conducted project-based learning to increase students' scientific thinking in three learning phases. Students were exposed to trainer kits in their study, so they directly experienced how to utilize such tools.…”
Section: Discussionsupporting
confidence: 71%
“…Some tools do not function properly. Based on observations and experience, it is shown that one of the learning media contained in the Workshop of the Department, namely the trainer kit for Electrical Lighting Installations, indicates the need to use learning media properly and correctly because these subjects are subjects that students will understand and master (Isnur Haryudo et al, 2021). The current trainer kit can be used quite well.…”
Section: Introductionmentioning
confidence: 99%